Model Mangsa Pemangsa dengan Pengaruh Musim - yudi Arpa; Muhammad Subhan; Riry Sriningsih (UNIVERSITAS NEGERI PADANG, 2014)
Abstract- Effect of season is one of the factors that need to be noted in the predation. In this study, used the four seasons, summer, winter, spring, and autumn, where the amount of predation different every season. The study began by establishing a mathematical model of predation to the effect of the season. In this model, the population is divided into two, prey populations and predator populations. With useful analysis model using perturbation theory note that the effect of the season had a significant effect on the growth patterns of prey and predator populations, where at any given time pattern of prey and predator population Growth Is changing. Keyword :Predator-Prey, Seasonal effect, Mathematical models, Perturbation theory.